Biosynthesis and axoplasmic transport of neurophysins in the hypothalamo-neurohypophysial system of Rana pipiens - Chang, AC (J Neurosci, 1984)
Biosynthesis, axoplasmic transport, and storage of neurophysin in the amphibian (Rana pipiens) magnocellular peptidergic neurosecretory system were studied, and the results were compared with those reported in mammals. After injection of [35S]cysteine into the preoptic recess, light microscopic autoradiography provides evidence that neurons of the preoptic nucleus (PON) synthesize cysteine-rich proteins. The time course of appearance of these [35S]cysteine-labeled proteins in different regions of the hypothalamo-neurohypophysial system was studied by slab gel autoradiography. [35S]Cysteine-labeled proteins were found in the PON less than 1 hr postinjection, whereas a major labeled protein, tentatively identified as the neurophysin, first appeared in the infundibulum and neural lobe 4 hr after the injection. In addition, the labeled neurophysin persisted in the neural lobe throughout the entire observation period of 5 days. The minimum transport rate for neurophysin was calculated as 0.9 mm/hr (22 mm/day) at 25 degrees C. Two different neurophysins (with isoelectric points (pI) 4.9 +/- 0.1, 4.6 +/- 0.1, and Mr = 23,000, 20,100) may be resolved from the neural lobe extracts by isoelectric focusing and SDS- polyacrylamide gel electrophoresis, respectively. In addition to the neurophysin peaks, two radioactive peaks with pI 5.2 and 5.8 may be detected in the preoptic nucleus and the infundibulum as early as 30 min after [35S]cysteine injection. Preliminary conversion studies suggest a putative precursor role for the pI 5.2 protein. The results indicate that in the amphibian peptidergic neurosecretory system, the synthesis of cysteine-rich neurophysin by the preoptic neurons, the transport through the infundibulum, and the storage in the neural lobe proceed similarily to their mammalian counterparts.